Project Come to the Wheel! - Viana, Elisangela Gomes; Martins, Silvana de Vitta; Garcia, Ana Paula Tamanaha; Naves, Fernanda Nazaré Arriel; Ribeiro, Geraldo Adolfo; Silva, Rosani Virgínia; Vasconcellos, Silvia Helena Santos; Gomes, Tatiane de Araújo (Seven Editora, 2023)
The E.E. Professor Francisco Pereira da Silva has been part of the Integral Education program since 2013, one of its strands being the Life Project. Given this, we thought of a project that could promote, in addition to self-knowledge, the scientific curiosity of students through research of articles related to their life projects. The Vem Pra Roda Project provides students with direct access to texts from scientific journals and books so that they can develop and expand their scientific language, in a differentiated way, and interdisciplinarity between the areas of knowledge: Natural Sciences and Mathematics, Language Codes and Human Sciences. It also stimulates the student to practice reading in a pleasurable way, making him acquire the habit of seeking knowledge through literatures with which he identifies, as well as establishing relationships with other contexts, stimulates the exchange of ideas, research and the continuous search for his life project through scientific research. It is understood that this project is relevant for students, because it researches texts of scientific subjects related to the students’ life project, which provides a more in-depth reflection, both oral and written, on the possible careers they will exercise. In this way, one can contribute to the formation of professionals who are aware and committed to society. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-093